2019
DOI: 10.1021/acs.jchemed.8b00728
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Virtual Reality Platform in Environmental Chemistry Education To Conduct a Field Trip to an Overseas Site

Abstract: Field trips are a common activity for instructors to engage students and give them a first-hand understanding of a subject, especially in environmental chemistry. However, the planning and execution for a field trip is logistically challenging and demanding of human and material resources. Here, we demonstrate the conduct of a virtual overseas field trip for 74 students with the use of a web-based virtual reality (VR) application. From the feedback after the virtual field trip, students reported general recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 14 publications
0
46
0
3
Order By: Relevance
“…Jolley, Kennedy, Reyna, et al [18] developed a VFT for tertiary students in an introductory-level geology course at the University of Canterbury. In a recent study [19], a virtual reality platform was applied in environmental chemistry education to conduct a field trip to an overseas site, thus reducing the associated costs and environmental impacts that would have been associated with an RFT. The VFT field trip, thus, presents an environmentally friendly yet innovative approach to allow learning among students, while minimizing the related contributions to GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Jolley, Kennedy, Reyna, et al [18] developed a VFT for tertiary students in an introductory-level geology course at the University of Canterbury. In a recent study [19], a virtual reality platform was applied in environmental chemistry education to conduct a field trip to an overseas site, thus reducing the associated costs and environmental impacts that would have been associated with an RFT. The VFT field trip, thus, presents an environmentally friendly yet innovative approach to allow learning among students, while minimizing the related contributions to GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the educational uses of 360 o videos, while not yet adequately systemized, seems to cover a rather wide and diverse set of learning domains and sciences. They are commonly used for delivering virtual tours to places of interest, museums, and archaeological sites (e.g., Argyriou et al, 2020;Skondras et al, 2019), as well as for presenting experiments and medical procedures (e.g., Ardisara & Fung, 2019;Sankaran et al, 2019). They have been also used for the teaching of subjects related to Ecology (e.g., Fokides & Kefalinou, 2020;Ritter et al, 2019), Physics (Wu et al, 2019), Physical Education (Kittel et al, 2020;Paraskevaidis & Fokides, 2020), Religion Education (Johnson, 2018), language learning (Berns et al, 2018;Xie et al, 2019), Public Health Education (Dawson et al, 2019), Safety Education (Pham et al, 2018), and for delivering virtual courses (Lee et al, 2017).…”
Section: O Videosmentioning
confidence: 99%
“…For example, they noted that the novelty of the experience (Lin et al, 2019) led to increased levels of enjoyment, satisfaction (e.g., Chang et al, 2019;Lee et al, 2017), and motivation (Fokides & Arvaniti, 2020;King-Thompson, 2017;Xie et al, 2019). In fact, students' responses regarding their experiences were highly positive, characterizing them as positive, useful, engaging, and that 360 o videos facilitated their comprehension/learning of the subjects they were taught (Fung et al, 2019;Huang et al, 2019;Ulrich et al, 2019). On the negative side, distraction and/or disorientation are significant issues (Ardisara & Fung, 2018).…”
Section: O Videosmentioning
confidence: 99%
“…For example, Bennie et al found that a virtual reality program was a better learning environment for visualization than traditional approaches such as molecular models, textbook images, and the computer-screen to teach enzyme kinetics [16]. Virtual reality also offers a way to provide a form of laboratory experience for online courses [17], and Fung et al found that using a virtual reality field trip for their environmental chemistry course was more convenient and less costly than its physical equivalent but produced comparable results [18].…”
Section: Virtual Reality and Augmented Realitymentioning
confidence: 99%